The Influence of Communication, Compensation, and Good Corporate Governance on Employee Performance - Kiki Rizki Yuliana; Qristin Violinda; Noni Setyorini (Yayasan Al Ma'arif Dawuhan, 2024)
This study aims to examine the influence of communication, compensation, and Good Corporate Governance on employee performance. The research involved 197 respondents selected using the Probability Sampling technique with the simple random sampling method. The analysis results show that the communication variable (X1) has a positive and significant influence on employee performance (Y) partially, with a significance value of 0.02. Conversely, the compensation variable (X2) does not affect employee performance (Y), with a significance value of 0.27. Meanwhile, the Good Corporate Governance variable (X3) has a positive and significant influence on employee performance (Y) partially, with a significance value of 0.00. This research can be a useful reference for other parties interested in conducting similar research in the future. The information and findings from this research can be a basis for further research and can be used as a guide in developing employee performance.